Inisiatif Standarisasi Waktu Pengumpulan Sampah di Kota Salatiga - Budiana, Mega Nora; Maryono, Maryono (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2017)
As in other cities, Kota Salatiga has the main problem in waste management which is the accumulation of waste in TPS which can cause water, soil and air pollution. Factors other than differences in waste management (waste collection community and Government waste processing) are the absence of scheduling arrangements and Standard Operating Procedures (SOPs) related to the standard time of garbage collection. The purpose of this research is to analyze the initiative of Salatiga City Government in creating standardization of waste collection. The identification of waste generation and distribution of waste collection time variation and the need of waste collection infrastructure is needed to analyze the initiatives of Salatiga City Government. The amount of waste generated from the extent of the land function shows that the region with the highest number of waste is the region with the highest population with its urban activity, and the opposite too. While the distribution of time variations vary compared to ideal circumstances that provide only one time variation based on the intensity of waste collection (60,69%). So from these two identifications can be formulated Salatiga Municipal Government initiative in reducing time variation imbalance with commitment to standardize waste collection time including technical and non technical preparation that can be applied.